2022
DOI: 10.1039/d2nr01516a
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly reconstructing the active surface of cobalt-based perovskites for alkaline seawater splitting

Abstract: As a potential oxygen evolution reaction (OER) catalyst, Co-based perovskites have received intensive attentions. However, Sr is readily to accumulate on their surface, then makes them inert toward OER. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Although perovskite oxides based on cobalt have shown a significant amount of potential in electrocatalysis, 203,204 their ability to accelerate NO 3 − electrochemical reduction to generate NH 3 has not been explored. Liu et al 205 have addressed this by proposing an effective strategy to promote NO 3 ER activity by adjusting the A-site deficiencies of cobalt-based perovskite oxides.…”
Section: Recent Progress In Ov-based Electrocatalysts In Electrochemi...mentioning
confidence: 99%
“…Although perovskite oxides based on cobalt have shown a significant amount of potential in electrocatalysis, 203,204 their ability to accelerate NO 3 − electrochemical reduction to generate NH 3 has not been explored. Liu et al 205 have addressed this by proposing an effective strategy to promote NO 3 ER activity by adjusting the A-site deficiencies of cobalt-based perovskite oxides.…”
Section: Recent Progress In Ov-based Electrocatalysts In Electrochemi...mentioning
confidence: 99%
“…These concerns have driven the exploration of several low-cost transition metal-based materials, among which transition metal (TM) oxides featuring a perovskite structure have attracted greater attention due to excellent OER performances, especially in alkaline media [8]. Recent reports have suggested that fine-tuning the perovskites can even surpass the best Ir/Ru-based OER catalysts [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%